2021
DOI: 10.1177/1744806921992620
|View full text |Cite
|
Sign up to set email alerts
|

Spinal GABAergic neurons are under feed-forward inhibitory control driven by Aδ and C fibers in Gad2 td-Tomato mice

Abstract: Background Spinal GABAergic neurons act as a critical modulator in sensory transmission like pain or itch. The monosynaptic or polysynaptic primary afferent inputs onto GABAergic neurons, along with other interneurons or projection neurons make up the direct and feed-forward inhibitory neural circuits. Previous research indicates that spinal GABAergic neurons mainly receive excitatory inputs from Aδ and C fibers. However, whether they are controlled by other inhibitory sending signals is not well understood. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Thus, it is likely that inhibitory axon terminals arising from neurons in laminae I–III can mediate GABA-only or mixed GABA-glycine synaptic events. However, in contrast to early [ 4 , 5 , 6 ] and recent [ 16 ] immunohistochemical findings, Miranda et al [ 26 ] recently reported that there are abundant axon terminals that are positive for GlyT2 and negative for GAD65/67 in laminae I–III, confirming electrophysiological data suggesting that in lamina II, the glycinergic component of inhibitory postsynaptic currents is as strong as (if not stronger than) the GABAergic component [ 1 , 70 ]. It has also been suggested that these glycine-only axon terminals may arise from neurons with cell bodies in lamina IV [ 26 , 47 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, it is likely that inhibitory axon terminals arising from neurons in laminae I–III can mediate GABA-only or mixed GABA-glycine synaptic events. However, in contrast to early [ 4 , 5 , 6 ] and recent [ 16 ] immunohistochemical findings, Miranda et al [ 26 ] recently reported that there are abundant axon terminals that are positive for GlyT2 and negative for GAD65/67 in laminae I–III, confirming electrophysiological data suggesting that in lamina II, the glycinergic component of inhibitory postsynaptic currents is as strong as (if not stronger than) the GABAergic component [ 1 , 70 ]. It has also been suggested that these glycine-only axon terminals may arise from neurons with cell bodies in lamina IV [ 26 , 47 ].…”
Section: Discussionmentioning
confidence: 84%
“…The importance of postsynaptic glycinergic inhibition in acute and chronic spinal pain processing has been substantiated by a great deal of experimental data [ 1 , 11 , 12 , 14 , 16 , 19 , 22 , 54 , 63 , 79 ]. Most of these studies have found that glycinergic postsynaptic inhibition affects various sets of excitatory interneurons, but reports about glycinergic innervation of inhibitory interneurons are sporadic [ 11 , 53 , 70 , 80 ]. Presumably, this is the reason why neural circuit models of spinal pain processing created to date do not include any representation of glycinergic disinhibition achieved by glycinergic inhibition of inhibitory interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify how CB 1 Rs participate in the mechanism by which cannabinoids mediated a sex difference, we then conducted an immunohistochemistry experiment to detect whether there were differences between males and females in CB 1 R expression in these GABAergic neurons. Given that GAD2‐tdTomato usually labels most GABAergic neurons (Liu et al., 2021). Using the FISH technique, we also detected the colocalization of GAD2‐tdTomato‐positive neurons with the CB 1 Rs mRNA probe and found that females had significantly more CB 1 R mRNA in the vlPAG compared to males ( t = 6.634; p < .001, n = 4, Figure 6a,b,e).…”
Section: Resultsmentioning
confidence: 99%
“…Most neurons in DH lamina II receive monosynaptic or polysynaptic inputs from C-primary afferents, with about three-quarters receiving monosynaptic C-fibers inputs. 61,93 Among these neurons, 30% to 80% are directly contacted by nociceptors expressing transient receptor potential vanilloid type 1 (TRPV1) 109,112 and more than 20% of GABAergic neurons in lamina II are contacted by Ad fibers. 93 Moreover, primary afferent fibers converge onto DH neurons, including fibers having distinct conduction velocities and stimulation thresholds.…”
Section: Convergence Of Sensory Afferents Onto Dorsal Horn Neuronsmentioning
confidence: 99%
“…61,93 Among these neurons, 30% to 80% are directly contacted by nociceptors expressing transient receptor potential vanilloid type 1 (TRPV1) 109,112 and more than 20% of GABAergic neurons in lamina II are contacted by Ad fibers. 93 Moreover, primary afferent fibers converge onto DH neurons, including fibers having distinct conduction velocities and stimulation thresholds. 61 This convergence is particularly large for C-fibers contacting islet cells in lamina II.…”
Section: Convergence Of Sensory Afferents Onto Dorsal Horn Neuronsmentioning
confidence: 99%